Investigation on improving mechanical properties of aluminium alloy sheet 5052-h32 for automotive application / Hidayat - Hidayat, - (2019)
The extensively used of Aluminum alloys are for numerous purposes because of their interesting compound of excellent particular strength, easy to shape, great manufacturing method, high electrical conductivity and availability in various applications, especially for automotive purpose. Aluminium Alloy Sheet 5052-H32 is studied in this research because it is one of the characters of material which is regularly applied for manufacturing automotive application. Two methods are used in this research, Anodization and Plasma Electrolyte Oxidation (PEO). The aims are to build the oxide layer on the surface of Al alloy sheet 5052-H32, also to analyze the microstructure and mechanical properties of deposited coatings as well as to compare the performance of anodization and PEO coating in Al alloy sheet 5052-H32. The oxide layer coating is seen by conducting surface characterization. The improvement of surface hardness by microhardness test from 35.3 HV to 65.8 HV for Anodization coating, and PEO coating is in the average of 67.9 HV. The adhesion test to determine the adhesion strength was achieved by the failure load was around 2023.9 mN for Anodization coating, and PEO coating slightly lower was around 2005.4 mN. The mechanical properties for the surface hardness and adhesion strength of aluminum oxide coated of Al alloy sheet 5052-H32 improved